Analisis Pemahaman Konsep Peserta Didik pada Pembelajaran Pendidikan Pancasila Kelas III Sekolah Dasar Negeri 09 Saruaso - Salsa Putri Nabila; Shellini Akmal; Sovie Dwi Putri Elma; Wandri Ramadhan (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2026)
This study aims to examine the conceptual understanding of third-grade students at SDN 09 Saruaso regarding the Pancasila Education subject. Employing a qualitative approach, data were collected through direct observation, brief interviews, and documentation. The results indicate that among the 12 student subjects, six fell into the medium category with a reasonably good level of understanding, four were in the high category demonstrating the ability to understand and apply Pancasila values ​​independently while two remained in the low category due to difficulties in grasping concepts deeply and relating them to real-world contexts. Factors influencing student understanding include teaching methods, learning media, motivation, and student engagement. The study provides empirical insights to assist teachers in designing more innovative and contextual learning strategies and offers a basis for schools to develop teacher training programs aimed at continuously improving the quality of Pancasila Education instruction.